2020
DOI: 10.1101/2020.09.04.282921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone tails cooperate to control the breathing of genomic nucleosomes

Abstract: Genomic DNA is packaged in chromatin, a dynamic polymer that forms fibers variable in size and compaction. Chromatin's monomeric unit, the nucleosome, is formed by wrapping ~ 146 basepairs of DNA around histone proteins. Dynamic transitions in the chromatin structure, which depend on intra- and inter-nucleosome dynamics and on chemical modifications of histones, are key to initiating gene regulation programs. The histone modifications occur in unstructured terminal regions known as tails and are key to epigene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 73 publications
3
27
0
Order By: Relevance
“…The position and conformation of the H3 and H2AC tails are critical for nucleosome breathing (25,34,35). We proposed that substantial, short lived opening of free nucleosomes is only possible when these tails establish a minimum number of interactions with the linker DNAs (25). Here we also observed that the long lived Oct4 mediated nucleosome opening depends on the mobility of histone tails.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The position and conformation of the H3 and H2AC tails are critical for nucleosome breathing (25,34,35). We proposed that substantial, short lived opening of free nucleosomes is only possible when these tails establish a minimum number of interactions with the linker DNAs (25). Here we also observed that the long lived Oct4 mediated nucleosome opening depends on the mobility of histone tails.…”
Section: Discussionsupporting
confidence: 53%
“…This demonstrates that the configurations of the H3 and H2AC tails are crucial for the initial nucleosome opening in the presence of Oct4. We recently showed that these tails modulate the intrinsic breathing of free nucleosomes (25). Taken together, our findings indicate that Oct4's ability to stabilize open nucleosome conformations depends on the nucleosome structural flexibility induced by histone tail mobility.…”
Section: Oct4 Modifies Nucleosome Structural Flexibilitysupporting
confidence: 57%
See 3 more Smart Citations